1998
DOI: 10.1002/(sici)1520-6807(199801)35:1<29::aid-pits3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum-based assessment of reading skills: Considerations and caveats for school psychologists

Abstract: General dissatisfaction with commercial norm‐referenced tests and global ability measures and the need for more specific achievement measures due to changes in special education have led to an increased interest in the curriculum‐based assessment of reading. We argue that a curriculum‐based assessment (CBA) of reading provides relevant information for instructional interventions only if the content of the curriculum and instruction are grounded in the cognitive skills underlying the domain of reading. If CBA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Curriculum-based measurement offers advantages to practicing school psychologists, as well. Concerns about the utility of commercially available normreferenced tests are well documented in the school psychology literature (see Deno, 1985;Howell, 1986;Peverly & Kitzen, 1998;Rosenfeld, 1987;Rosenfeld & Shinn, 1989;Shapiro, 1990;Shapiro & Elliott, 1999). Of particular interest is their limited value for making instructional recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Curriculum-based measurement offers advantages to practicing school psychologists, as well. Concerns about the utility of commercially available normreferenced tests are well documented in the school psychology literature (see Deno, 1985;Howell, 1986;Peverly & Kitzen, 1998;Rosenfeld, 1987;Rosenfeld & Shinn, 1989;Shapiro, 1990;Shapiro & Elliott, 1999). Of particular interest is their limited value for making instructional recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that texts with more complex syntactical structures may be more difficult for children to read . 'Where the child's language skill is found to be limited' (Clay, 1971, p. 68) or children who have not developed a sound understanding of grammatical rules (Peverly & Kitzen, 1998) and 'the ability to maintain strong grammatical relationships when reading may contribute more to reading than previously realised' (Adams, 1990, cited in Beatty & Care, 2009.…”
Section: Analysis Of Complexity In Verbal Segments Of Textmentioning
confidence: 99%
“…CBA has the dual purpose of identifying struggling readers and evaluating the effectiveness of instruction (i.e., change in the readers' skills over time). Peverly and Kitzen (1998) suggested that CBA alone is insufficient to ensure the effectiveness of instruction and that attention must also be given to the cognitive processes that underlie reading skills. Thus, Tier 1 assessment provides early screening of all students, from kindergarten through third grade, for indicators of cognitive processing weaknesses (e.g., phonological processing, rapid automatic naming, graphomotor fluency, vocabulary).…”
Section: Assessment: Screening For Learning and Behaviormentioning
confidence: 99%
“…Traditional approaches to assessment (i.e., observation) would include, for example, charting student behaviors indicative of engaged time and a focus on teachers' interactions with students regarding their behaviors. However, ensuring positive student outcomes requires going beyond these data (Peverly & Kitzen, 1998), particularly with regard to African American students. Here, we need to recognize the unique characteristics needed for curriculum and instruction that affirms children's cultures.…”
Section: Assessment: Screening For Learning and Behaviormentioning
confidence: 99%